Application of a compressed-sensing (CS)-based deblurring scheme to digital tomosynthesis (DTS) for improved x-ray nondestructive testing: Simulation and experimental studies. (November 2016) - Kim, K.S.; Park, S.Y.; Kim, G.A.; Cho, H.S.; Je, U.K.; Park, Y.O.; Park, C.K.; Lim, H.W.; Woo, T.H.; Park, S.M.; Lee, H.W.; Seo, C.W.
Abstract: In this work, we investigated a compressed-sensing (CS)-based deblurring scheme for image deblurring of high accuracy in digital tomosynthesis (DTS). We implemented the proposed deblurring scheme and performed a systematic simulation to demonstrate its viability for improved x-ray nondestructive testing. We also performed an experiment by using a table-top setup which consists of an x-ray tube (90 kVp, 6 mAs) and a CMOS-type flat-panel detector having a 198-μm pixel resolution. In both the simulation and the experiment, 51 projection images were taken with a tomographic angle range of θ =60° and an angle step of Δ θ =1.2° and then deblurred by using the proposed algorithm before performing the common filtered-backprojection (FBP)-based DTS reconstruction. Our results indicate that the proposed deblurring scheme appears to be effective for the blurring problems in DTS and is applicable to improve the image characteristics in the present x-ray nondestructive testing. Highlights: The compressed-sensing (CS)-based deblurring scheme is studied for image deblurring. Digital tomosynthesis (DTS) is applied for the x-ray nondestructive testing. A table-top setup of an x-ray tube and a CMOS-type flat-panel detector are used. The proposed deblurring scheme appears to be effective for the blurring problems.